Regioselective C(sp2)–H imidation of arenes by redox neutral visible-light photocatalysis. Issue 3 (20th December 2022) - Ghosh, Manoj Kumar; Sharma, Kumari Swati; Pandey, Ganesh
Abstract : A redox neutral visible light-induced regioselective C(sp 2 )–H imidation of electron-rich arenes and heteroarenes using conceptually designed redox-active imide as the N-centered imidyl radical source is reported. Abstract : We report herein a redox neutral visible light-induced regioselective C(sp 2 )–H imidation of electron-rich arenes and heteroarenes using conceptually designed redox-active 1 as a source of the N-centered imidyl radical. Structurally diverse aromatic imides were obtained in moderate to good yields. This methodology has been successfully employed for the late stage imidation of complex molecules and has also been applied towards the formal total synthesis of the marine natural products carpatamides A, B and D. It has further been shown that the generated imides can easily be converted to the corresponding anilines in situ directly.